Sagip Putla (an anemia detection and tretment program) The Bulakan, Bulacan Experience (Philippine Journal of Nutrition, 2011)
A study on the Sagip Putla program among pregnant women in Bulakan, Bulacan was conducted to characterize implementation of the program as it has been devolved from the provincial to the community level along the FOURmula One for Health framework as a tool. Service providers and consumers involved in the program served as respondents. A combination of data collection procedures was utilized. Descriptive statistics and correlation analysis were employed to interpret results. Results showed that the program is continuously implemented as an integral part of the routine health service. F1s pillar on regulation was reflected through the revised guideline, recording and reporting systems, and conduct of information dissemination activities. In terms of financing, standard procedures for budget allocation and procurement were followed whereas for governance, capacity building activities, and coordination were not given much attention. Service delivery was illustrated through the different program activities as it is extended by the providers to consumers. This study reveals that Sagip Putla as a community-based supplemental iron program can still be improved. Consumer behavior and program management should be given important consideration.